VOCATIONAL FACTORS IN DISABILITY CLAIM ASSESSMENT: A COMPARATIVE SURVEY OF 11 COUNTRIES. - Rajnes, David; Notaro, Tony (Social Security Bulletin, 2019)
Public disability benefit programs in the United States and other countries consider, as a condition for benefit eligibility, the claimant's ability or inability to resume or find work because of a health impairment. Many countries use an applicant's vocational factors (VFs)--age, education, and work experience--in assessing disability claims. As such, VFs play an important role in determining who qualifies for disability and related benefits. This article offers a comprehensive examination of the disability assessment processes in 11 developed countries and highlights the use and relevance of VFs in those processes.